“The Innate Tail”: An Unusual Cause of Rectal Bleeding in an Adult Male - Nair,Sujit Padmanabhan (2021)
Abstract: Retrorectal cystic hamartomas or tailgut cysts are infrequent congenital lesions presenting as presacral masses originating from the embryonic hindgut. They are commonly diagnosed in middle-aged women. Physicians must have a high index of suspicion to diagnose this rare tumor. We report a case of retrorectal hamartoma in a 70-year-old male presenting as rectal bleeding instead of the usual compressive symptoms. The utility of imaging modalities and the paramount importance of histopathology has been described. The treatment modality is surgical excision to prevent the potential malignant transformation.